Developing Scriptural Agency Through Participatory Action Research Embedded In Service Learning - Jaffer, Saleemah; Bayat, Abdullah (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2023)
This study addresses the gap in Islamic higher education, where learning often emphasizes theoretical knowledge rather than practical application, by exploring the development of scriptural agency through participatory approaches. The purpose of this study is to examine how integrating Community-Based Participatory Action Research (CBPAR) within a service learning module can enhance students’ ability to apply scriptural knowledge in real-life contexts. Using a self-study case study design, the research focuses on students at an Islamic higher education institute in South Africa, combining experiential learning principles with reflective and collaborative activities. The findings reveal that students developed stronger agency, reflected in increased confidence, critical reflection, and the capacity to translate religious teachings into meaningful community engagement. Additionally, students improved essential skills such as teamwork, communication, and problem-solving through direct involvement in community-based projects. The study highlights that learning faith becomes more meaningful when practiced in real contexts. This research contributes to the field of Islamic education by emphasizing the importance of shifting from traditional rote learning to applied, experiential pedagogies, thereby fostering socially responsible graduates and supporting sustainable community development.